2012
DOI: 10.1002/dvdy.23903
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific responses to aberrant FGF signaling in complex head phenotypes

Abstract: Background The role of fibroblast growth factor and receptor (FGF/FGFR) signaling in bone development is well studied, partly because mutations in FGFRs cause human diseases of achondroplasia and FGFR-related craniosynostosis syndromes including Crouzon syndrome. The FGFR2c C342Y mutation is a frequent cause of Crouzon syndrome, characterized by premature cranial vault suture closure, midfacial deficiency and neurocranial dysmorphology. Here, using newborn Fgfr2cC342Y/+ Crouzon syndrome mice, we tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 57 publications
4
73
2
Order By: Relevance
“…In animal models for human craniosynostosis syndromes, the abnormal skull shape can be detected before the premature closure of cranial vault sutures 71•, 72•]. The development of animal models for craniosynostosis [70, 73, 74] has already revealed many molecularly driven three-dimensional morphological changes in soft tissues of the head and skull that were not apparent in humans [71•, 75, 76•, 77]. These changes are more difficult to evaluate quantitatively in humans where observations are routinely made postnatally and there is a lack of appropriate morphological control data sets to make meaningful comparisons to abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models for human craniosynostosis syndromes, the abnormal skull shape can be detected before the premature closure of cranial vault sutures 71•, 72•]. The development of animal models for craniosynostosis [70, 73, 74] has already revealed many molecularly driven three-dimensional morphological changes in soft tissues of the head and skull that were not apparent in humans [71•, 75, 76•, 77]. These changes are more difficult to evaluate quantitatively in humans where observations are routinely made postnatally and there is a lack of appropriate morphological control data sets to make meaningful comparisons to abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…FGF/FGFR signaling is known to be complex, and tissue-specific responses are widespread and variable (Wilke et al, 1997; Ornitz and Marie, 2002; Dorey and Amaya, 2010; Hébert, 2011; Martínez-Abadías et al, 2011; Martínez-Abadías et al, 2013). The identity of FGFs expressed during early craniofacial morphogenesis and palatal formation have been extensively characterized (Britto et al, 2002; Bachler and Neubüser, 2001; Welsh et al, 2007), but the complement of FGFs expressed in the facial sutures during late embryological development is undefined.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Several studies reported abnormalities of the skull 2,5,9,28,29 and skull base 9,13,30 in Crouzon syndrome in humans and in mice. [31][32][33] Thus, it is likely that FGFR2 gene mutations have an effect on hindbrain development and give rise to abnormal growth of its surrounding bone plates (i.e., the foramen magnum). Although there are various publications concerning the cranial base in mice and humans, little has been written about the cranial base in Crouzon patients, not to mention about the intraoccipital synchondroses in these patients.…”
Section: Discussionmentioning
confidence: 99%